An idealised study for the evolution of a shoreface nourishment. (1st May 2019) - Chen, W.L.; Dodd, N.
Abstract: We develop an idealised one dimensional (cross-shore) morphodynamic model that couples wave, tide and sediment dynamics to study the effect and evolution of a shoreface nourishment. Sediment fluxes driven by wave skewness, wave asymmetry (both onshore) and return flow (offshore) are considered. With the aid of new analytical expressions for the skewness and standard deviation of wave velocity and acceleration, sediment fluxes are calculated. Nourishment is viewed as a perturbation to the system in equilibrium that is subject to the divergence of the perturbed sediment flux and a gravity driven diffusion term. Depending on the location, a nourishment may provide a feeder or lee effect. In moderate and mild wave conditions, the evolution of a nourishment primarily depends on the relative location of nourishment and break point. Placed well offshore of the break point, the nourishment induces an overall positive perturbation in sediment flux, resulting in onshore migration (feeder effect). Located closer to the break point, the nourishment induces an earlier wave breaking, which dissipates part of the wave energy (lee effect), leading to a negative sediment flux perturbation around this break point and a positive sediment flux perturbation around the break point of the un-nourished beach. Depending on the intensity of the earlier breaking, the nourishment either migrates onshore (weak break) or splits into onshore and offshore moving parts (strong break). The relative importance of the diffusion term and the divergence of perturbed sediment flux may lead to a primarily migrating or decaying evolution of nourishment. In storm wave conditions, the nourishment tends to move offshore due to the predominance of return flow driven sediment flux. The sensitivity to wave period and tide are also studied. Model results are consistent with observations, as well as prevailing theory on cross-shore sediment transport. Highlight: An idealised one dimensional (cross-shore) morphodynamic model that couples wave, tide and sediment dynamics is developed to study the e_ect and evolution of a shoreface nourishment. In moderate and mild wave conditions, a nourishment placed well o_shore from the break point induces an overall positive perturbation in sediment ux, resulting in onshore migration (feeder e_ect). Located closer to the break point, the nourishment induces an earlier wave breaking, which dissipates part of the wave energy (lee e_ect), resulting in onshore migration (weak break) or splitting into onshore and o_shore moving parts (strong break). In storm wave conditions, nourishment moves o_shore due to the predominance of return-ow-driven sediment ux. Tide a_ects nourishment evolution through shifting the relative location of the nourishment and break point. The sediment dynamics at low tide dominate the evolution of the nourishment.